Shifting Norms and Sensitivity of the Jomok Meme: Critical Multimodal Discourse Analysis - Andika Pratama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to reveal a specific and contextual flow of interpretation within the controversial phenomenon frequently referred to as the Jomok meme. These memes, which are closely identified with figures such as Amba, Rusdi, Mas Fuad, and others, are often invoked when a meme relates to elements of gay or homosexual jokes featuring specific Black actors. This research employs a qualitative descriptive approach using netnographic methods for data collection and purposive research sampling. Data analysis was conducted through Teun A. Van Dijk’s Socio-Cognitive model. This research is also complemented by Kress & Van Leuween's visual grammar framework and Jean Baudrillard's Simulacra concept. A total of 10 data samples were analyzed (memes and comments). This research produces findings that the cognitive processes within the readers' mental models are reciprocal, dissociative, and reconstructive. This study contributes to the increasingly complex field of digital meme discourse recently, through the phenomenon of shifting digital community norms with the emergence of communities of fans of homosexual and vulgar memes.